Poverty alleviation and the degree of centralisation in European schemes of social assistance - Katja Hölsch; Margit Kraus (Luxembourg Income Study (LIS), 2003)
In this paper, the relationship between the degree of centralisation and the distributive outcomes in European schemes of social assistance is investigated. For this purpose, a scheme of classification suitable for grouping the EU15 schemes according to features related to centralisation is established by using cluster analysis and an indicator for centralisation is developed by employing multidimensional scaling. Subsequently, on the basis of LIS data the effectiveness and efficiency in reducing poverty through social assistance payments are calculated using several measures of poverty for five selected EU systems and the linkage of their distributive impacts to the degree of centralisation is examined. Concerning effectiveness in poverty alleviation, the results provide some evidence that extremely centralised systems are more effective with regard to redistribution than extremely decentralised schemes. However, for systems with a medium degree of centralisation, the hypothesis that greater decentralisation leads to more effectiveness is not supported. With respect to efficiency, no support is lent to the hypothesis that a higher degree of decentralisation is accompanied by a better distributive efficiency. Rather, the results seem to suggest that systems with a medium degree of decentralisation do better than either extremely centralised or extremely decentralised systems.
Keywords: I32; I38; H53; 330; Social Assistance; Classification; Centralisation; Poverty; Redistribution; Sozialpolitik; Einkommensumverteilung; Zentralisierung; Föderalismus; Wirkungsanalyse; Armut; Einkommensverteilung; Schätzung; EU-Staaten